Performance of layers submitted to different forced-molting methods and different temperatures - Sgavioli, S [UNESP] (2011)
This study was carried out to evaluate the performance and egg quality of laying hens, in their second laying cycle submitted to different forced-molting methods and three environmental temperatures. Six hundred layers were distributed in a completely randomized experimental design with 15 treatments with five replicates of eight birds each, according to 5x3 factorial arrangement (molting methods vs. temperatures). The following forced-molting methods were applied: 90%, 70%, 50% dietary alfalfa inclusion, addition of 2,800 ppm zinc, and feed fasting. Temperatures were: 20 ºC, 27 ºC and 35 ºC. At the end of each period of the second laying cycle, bird performance and egg quality were evaluated. Data were submitted to analysis of variance and means were compared by orthogonal and polynomial contrasts. The highest alfalfa inclusion level (90% alfalfa and 10% basal diet) proved to be efficient as compared to the other methods, independently of temperature.